Toward the Design of a Catalytic Metallodrug: Selective Cleavage of G‐Quadruplex Telomeric DNA by an Anticancer Copper–Acridine–ATCUN Complex1. Issue 6 (11th December 2014) - Yu, Zhen; Han, Menglu; Cowan, James A.
Abstract: Telomeric DNA represents a novel target for the development of anticancer drugs. By application of a catalytic metallodrug strategy, a copper–acridine–ATCUN complex (CuGGHK‐Acr) has been designed that targets G‐quadruplex telomeric DNA. Both fluorescence solution assays and gel sequencing demonstrate the CuGGHK‐Acr catalyst to selectively bind and cleave the G‐quadruplex telomere sequence. The cleavage pathway has been mapped by matrix assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) experiments. CuGGHK‐Acr promotes significant inhibition of cancer cell proliferation and shortening of telomere length. Both senescence and apoptosis are induced in the breast cancer cell line MCF7. Abstract : A copper–acridine–ATCUN complex selectively binds and cleaves the G‐quadruplex telomere sequence of DNA. The cleavage pathway has been mapped by MALDI‐TOF MS experiments. The complex promotes significant inhibition of cancer cell proliferation and telomere shortening, inducing both senescence and apoptosis in the MCF7 cancer cell line.